The Ideology of the Aesthetics - Eagleton, Terry (Cambridge Blackwell, 1990)
The Ideology of the Aesthetic presents a history and critique of the concept of the aesthetic throughout modern Western thought. As such, this is a critical survey of modern Western philosophy, focusing in particular on the complex relations between aesthetics, ethics and politics. Eagleton provides a brilliant and challenging introduction to these concerns, as characterized in the work of Kant, Schiller, Schopenhauer, Kierkegaard, Marx, Nietzsche, Freud, Heidegger, Lukacs, Adorno, Habermas, and others.
Keywords: Esthetics